A New Era in the Foreign Policy of China: Concept of “Community of Common Destiny” - А.К. Нуридденова (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2019)
This article systematically explores the origins, the content, the goal, and the foreign policy impact of the concept of ‘community of common destiny’ that has become central to the contemporary foreign policy of China. On the basis of the works developed by the Chinese, Western and Kazakhstani scholars on this topic, the author alludes that the concept of ‘community of common destiny’ indicates the start of the new era in China’s foreign policy. This research finds that this new concept made China divert from its previously dominant foreign policy principle of “keeping a low profile” and pushed for more active foreign policy conduct. It concludes that the active popularization of this new concept at major international events by the Chinese leadership signifies China’s willingness to act according to its growing international clout.